PRODUCTION AND OPTIMIZATION OF GLUCONIC ACID IN BATCH FERMENTATION BY ASPERGILLUS NIGER - KULANDAIVEL, S.; PRIYA, P.MOHANA (Innovare Journal of Life Sciences, 2014)
Abstract The optimization study of gluconic acid fermentation was carried out using Aspergillus niger at three different carbon sources. The experimental study was conducted with different glucose concentration, pH, temperature, age of culture, agitation and volume of inoculums with a continuous shaking flask method. Gluconic acid production was affected by increase of carbon concentrations at the same time fermentation time also increased. The siginificant level of gluconic acid (148 g/L) production was observed at 96 hrs with maximum 84% of glucose conversion. The gluconic acid yield/gram of glucose feeding was 74%. The isolated fungus has the capacity to produce maximum amount of gluconic acid.Â